Will Tanner: Pray for Death - Book 6 - Johnstone, William W.; Johnstone, J. A. (New York, NY : Pinnacle Books, Kensington Publishing Corp., 2020)
"Theres serious trouble brewing in the Choctaw nation, and it goes by the name of Tiny McCoy. This small-time cattle rustler is expanding his brand by brewing batches of whiskey in the Chocktaw territory of Muddy Boggy Creek. Tiny and his partner have also turned the illegal brewery into a robbers roost for outlaws, cutthroats, and killers of every bent. Local lawman Jim Little Eagle is under attack and out-gunned. But when he sends a wire to Fort Smith asking for backup--and the U.S. Deputy Marshal Tanner shows up, Little Eagle knows theyre in for one hell of a bloodbath. If anyone can drive those murdering devils to their knees and saying their prayers, its Will Tanner."--Back cover.
Keywords: United States marshals -- Fiction; Cattle stealing -- Fiction; Brigands and robbers -- Fiction; Brewing -- Fiction; Fiction; Western fiction; Western fiction